Exploring the experiences of Saudi mothers in the United States regarding the use of social networking sites of their adolescents - Hannon, Ragad Abdul-Hameed (Kansas State University, 2018)
We live in an era of constant communication, where Social Networking Sites (SNSs) are part of the technology revolution that has significantly altered our lives and means of communication. Adolescents are quick adopters of these sites; they spend a lot of their daily time interacting via these sites. Most parents in the United States strive to understand the purpose and function behind their children’s use of these technologies. This study is aimed to explore the Saudi mothers’ experiences with their adolescents in a different culture and country. The study focused on exploring the experiences, concerns, social and technical challenges, and strategies of Saudi mothers in the United States by using qualitative methodology. A snowball strategy was used through specific Saudi student groups and organizations in the United States. The participants recruited were Saudi mothers (N=13) who had adolescents (their ages are between 10- and 17-years-old). The interviews were transcribed verbatim, coded, and analyzed in light of symbolic interaction theory. The findings revealed some benefits of using SNSs among adolescents such as learning new languages or practicing the adolescent's native language. On the other hand, the findings also showed great concern among mothers and a lot of challenges about their adolescents’ use of SNSs. Also, the findings showed the roles of these mothers to protect, advise, and support their children regarding the use of SNSs. Mothers confirmed that their adolescents using SNSs without control or supervision may cause a lot of problems that affect adolescents, parents, and the relationships between them.
Keywords: Social networking sites; Adolescent; Saudi mothers; SNS; Family life education; Adolescence